1988
DOI: 10.1017/s0043174500074609
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Release of Three Herbicides by the Kraft Lignin PC940C

Abstract: A pine kraft lignin (PC940C) controlled the release of14C-chloramben (3-amino-2,5-dichlorobenzoic acid),14C-metribuzin [4-amino-6-(1,1-dimethylethyl)-3-(methylthio)-1,2,4-triazin-5(4H)-one], and14C-alachlor [2-chloro-N-(2,6-diethylphenyl)-N-(methoxymethyl)acetamide] as measured by water leaching in soil columns. As more PC940C was used, a concentration effect was found with more of the three herbicides being retained in the top portion of the soil columns. Combinations of alachlor and metribuzin applied with P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
21
0

Year Published

1996
1996
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 10 publications
3
21
0
Order By: Relevance
“…When MEFs were applied, the herbicide eluted was significantly less than that from the CF ( Table 2), the rest remaining distributed among the different depths in the soil column ( Table 4). This is supported by previous studies, which indicated that alachlor leaching can be reduced by microencapsulation techniques (6,(17)(18)(19)(20). As observed in Figure 2a, the maximum of the BTC obtained from CF occurs earlier (about 4 pore volumes) than for the rest of the formulations, with the exception of A8, indicating that the microencapsulated formulations result in higher soil retention and slower release.…”
Section: Alachlor Encapsulation In Ethylcellulose Microspheressupporting
confidence: 87%
“…When MEFs were applied, the herbicide eluted was significantly less than that from the CF ( Table 2), the rest remaining distributed among the different depths in the soil column ( Table 4). This is supported by previous studies, which indicated that alachlor leaching can be reduced by microencapsulation techniques (6,(17)(18)(19)(20). As observed in Figure 2a, the maximum of the BTC obtained from CF occurs earlier (about 4 pore volumes) than for the rest of the formulations, with the exception of A8, indicating that the microencapsulated formulations result in higher soil retention and slower release.…”
Section: Alachlor Encapsulation In Ethylcellulose Microspheressupporting
confidence: 87%
“…Dorado et al (2005) reported a similar result for the sorption of both pesticides by soils modifi ed with manure and straw. Th e partial sorption re- versibility of linuron from lignins could be due to the sorption of linuron by low-molecular-weight water-soluble materials (Riggle and Penner, 1988;Sánchez-Camazano et al, 2000). Figure 2 shows the isotherms corresponding to the sorption of paraquat (cationic) and dicamba (anionic) by the lignins and cellulose.…”
Section: Sorption-desorption Of Non-ionic Pesticides By Organic Matermentioning
confidence: 99%
“…However, studies on pesticides, compounds with large complex structures with different functional groups able to interact with such organic components, are less common. In general, the aim of the studies performed has been to determine the behavior of lignins as pesticide support in controlled‐release formulations (Riggle and Penner, 1987, 1988; Ferraz et al, 1997) or to evaluate their influence as a precursor of the soil organic matter (OM) in the determination of pesticide behavior in soils (Benoit et al, 1999; Beulke et al, 2005). The mechanism of action governing the retention of pesticide by these materials has been scarcely addressed (Torrents et al, 1997).…”
mentioning
confidence: 99%
“…11 Furthermore, a controlled‐release system not only increases the effectiveness of the active agents, but it also facilitates minimizing the amount of chemicals applied to the soil, and thus, decreases the likelihood of damage to the environment. 12 Unlike conventional products, controlled‐release materials are safer for those who handle them or come in contact with treated crops during harvesting or storage. 13 The application of controlled release technology has been slow to reach commercialization, despite interesting research and development work by the major agrochemical companies over the last 10 years.…”
Section: Introductionmentioning
confidence: 99%